2014
DOI: 10.7314/apjcp.2014.15.9.4085
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Atelectasis and Primary Tumor Glycolysis on F-18 FDG PET/CT on Survival in Lung Cancer Patients

Abstract: Background: Atelectasis is an important prognostic factor that can cause pleuritic chest pain, coughing or dyspnea, and even may be a cause of death. In this study, we aimed to investigate the potential impact of atelectasis and PET parameters on survival and the relation between atelectasis and PET parameters. Materials and Methods: The study consisted of patients with lung cancer with or without atelectasis who underwent 18 F-FDG PET/CT examination before receiving any treatment.18 F-FDG PET/CT derived param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…PET/CT scans are a widely accepted tool for staging and assessing the response to cancer therapy, and 18F-FDG is the most widely using PET tracer in clinical oncology (Hasbek et al, 2014). It also can be useful for cancer screening and evaluating the whole body and performed in Japan reported that FDG-PET/CT scans could detect prostate cancer cases that had a high Gleason score (≥7).…”
Section: Discussionmentioning
confidence: 99%
“…PET/CT scans are a widely accepted tool for staging and assessing the response to cancer therapy, and 18F-FDG is the most widely using PET tracer in clinical oncology (Hasbek et al, 2014). It also can be useful for cancer screening and evaluating the whole body and performed in Japan reported that FDG-PET/CT scans could detect prostate cancer cases that had a high Gleason score (≥7).…”
Section: Discussionmentioning
confidence: 99%
“…
Hasbek et al, 2014). However, the prognostic significance of the SUVmax based on the histologic type has not yet been fully elucidated.
…”
mentioning
confidence: 99%
“…Atelectasis has been reported as a prognostic factor in other types of lung cancer. More specifically, atelectasis has been shown to be associated with the prolonged survival of patients with non-small cell lung carcinoma (NSCLC) (22)(23)(24)(25) even at advanced stages (26).…”
Section: Discussionmentioning
confidence: 99%